Effect of methamphetamine exposure during prenatal and preweaning periods lasts for generations in rats - Slamberová, Romana; Pometlová, Marie; Rokyta, Richard (Developmental psychobiology, 2007)
Our previous studies demonstrated that methamphetamine (MA) administration during gestation and/or lactation affects maternal behavior in rats and that birth weight and sensory-motor coordination of their pups are also influenced. The present study tested the hypothesis that the effect of MA induces long-term changes affecting second generation of rats that were not exposed to the drug. Adult females exposed during prenatal and preweaning periods to 5 mg/kg MA daily, were examined for regularity of estrous cycle and mated with stimulus, unexposed males. Dams (nontreated absolute control, saline- and MA-exposed) were observed with their pups in two tests of maternal behavior (observational and retrieval tests). Their pups were further tested throughout the preweaning period to examine their development. Our data demonstrate that MA-exposed mothers displayed more nursing, were more often in the nest and in contact with their pups, and were faster in retrieving their pups than saline-exposed and/or control mothers. There were no differences in litter characteristics, birth weight and weight gain of pups between groups. Interestingly, pups from mothers exposed to MA during prenatal and preweaning period had impaired sensory-motor coordination. They achieved righting reflex in mid-air later than both control groups. Additionally, they had more falls in rotarod and bar-holding tests than pups from both control and saline-exposed mothers. In homing performance, pups from MA- and saline-exposed dams learned slower to return to the home box than pups from control dams. Thus, the present study demonstrates that MA abused by mothers may affect two generations of their offspring.
Keywords: reakční čas; posturální rovnováha; Prenatal Exposure Delayed Effects; Animals, Newborn; Male; Rats, Wistar; Psychomotor Performance; zpožděný efekt prenatální expozice; retence (psychologie); psychomotorický výkon; Pregnancy; těhotenství; vztah mezi dávkou a účinkem léčiva; Homing Behavior; Reaction Time; mužské pohlaví; Motor Skills; potkani Wistar; Mental Recall; mateřské chování; novorozená zvířata; teritoriální chování; Postural Balance; Maternal Behavior; rozpomínání; krysa rodu Rattus; Central Nervous System Stimulants; methamfetamin; Animals; stimulanty centrálního nervového systému; Methamphetamine; ženské pohlaví; zvířata; Rats; Retention, Psychology; motorické dovednosti; Female; Dose-Response Relationship, Drug